The Enactment of Pedagogical Competence among Certified EFL Teachers at Secondary Schools - Agussatriana Agussatriana; Andi Patmasari; Abdul Kamaruddin; Nadrun Nadrun; Muhammad Ismail (Datokarama English Education Journal, 2026)
The enhancement of teachers’ competence and performance has been a primary objective of Indonesia’s teacher certification program (PPG). This study aimed to describe and interpret certified teachers’ professional competencies as reflected in their classroom practices and teaching performance. Employing an explanatory mixed-method design, the study integrated qualitative interviews to explain specific trends identified in the quantitative phase. Data were collected from 15 certified English teachers enrolled in the 2021 PPG program at Tadulako University, selected through purposive sampling. The instruments used to collect data were questionnaires and semi-structured interviews. The data collected from this study were analyzed both quantitatively and qualitatively. The questionnaire data were processed and statistically analyzed, while the interview data were analyzed qualitatively. Based on the data analysis, the participating teachers perceived themselves as having pedagogical, personal, social, and professional competencies and had implemented them in the teaching and learning process. Furthermore, in terms of teacher performance – including lesson planning, teaching implementation, learning evaluation, and task discipline – the teachers could be considered competent.